PSIII-9 Performance by weaned Katahdin lambs offered diets with and without Actifor® Pro. (30th November 2020) - Edwards, Kandace; Shanks, Bruce C; Caldwell, James D; Adams, Kevin
Abstract: Using all-natural phytogenics could be an alternative to using growth promotors within animal agriculture; particularly, since consumers are becoming more concerned with the use of these types of products. Our objective was to determine if using Actifor ® Pro (PRO) could improve weaned lamb performance. On June 17 th, 2019, a total of 60 (18 ± 0.92 kg BW) Katahdin ram lambs were weaned and stratified by BW and allocated randomly to 1 of 10 groups representing 2 treatments: 1) C (no PRO added; n = 5) and 2) PRO (5 g/hd/d; n = 5). During the 84-d study, lambs were housed in 2.4 × 4.9-meter pens and offered a 16% CP commercial grower diet. All lambs had ad libitum access to feed and water. Prior to the start of the study, all lambs were administered a CD&T vaccine plus drenched with an oral dewormer. Lambs were weighed at the start, d 28, d 56, and at the end of the study. Data were analyzed using Proc Mixed of SAS with pen(treatment) as the error term. Start, d 28, d 56, final BW, d 56 gain, d 56 ADG, final gain, and final ADG did not differ (P ≥ 0.31) between treatments. However, d 28 gain and d 28 ADG tended (P = 0.07) to be greater from PRO compared with C. Intake and G:F did not differ (P ≥ 0.19) between treatments throughout the study. Therefore, feeding Actifor® Pro may improve gain within the first 28 days after weaning, but those difference may not persist throughout the growing phase. Furthermore, this product may need to be investigated in a creep feed diet.